(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This article explores the various types of assimilation of folklorisms in the poem “Mangi bulak” by Ibragim Yusupov. Folklorisms are cultural elements derived from folklore, such as proverbs, idioms, and traditional beliefs. The study aims to analyze how these folklorisms are incorporated into I. Yusupov’s poem and the impact they have on its meaning and cultural significance. Through a detailed examination of linguistic and contextual aspects, this article sheds light on the role of folklorisms in enriching literary works and preserving cultural heritage.